Spin Susceptibility in Neutron Matter from Quantum Monte Carlo Calculations - Luca Riz; Francesco Pederiva; Diego Lonardoni; Stefano Gandolfi (Particles, 2020)
The spin susceptibility in pure neutron matter is computed from auxiliary field diffusion Monte Carlo calculations over a wide range of densities. The calculations are performed for different spin asymmetries, while using twist-averaged boundary conditions to reduce finite-size effects. The employed nuclear interactions include both the phenomenological Argonne AV8′ + UIX potential and local interactions that are derived from chiral effective field theory up to next-to-next-to-leading order.